Optimalisasi Pemasangan Panel Solar Home System Untuk Kehidupan Masyarakat Pedesaan di Ban Kubu Karangasem - Nugraha, I Made Aditya; Ridhana, Pt Aries; Listuayu, Kadek (Majalah Ilmiah Teknologi Elektro, 2018)
The power and energy output of a Solar Power Plant or SHS is influenced by several factors, such as temperature, solar light intensity, solar panel orientation, solar panel angle, wind speed and Earth's atmosphere. From six samples of SHS in Desa Ban Kubu Karangasem using Friedman Analysis, and continued with Post Hoc Wilcoxon test, the result p is <0.001. From these results it can be seen that there is a significant difference for the voltage, current, power and energy generated by each SHS. This difference causes the electric energy generated by SHS is also different, thus affecting the needs of electric energy and people's lives every day. To overcome this, then for planning and development of SHS for rural communities in the future more optimized so that the energy can be enjoyed by the community more optimal and efficient